2011
DOI: 10.1016/j.drugalcdep.2010.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Directly observed antiretroviral therapy improves adherence and viral load in drug users attending methadone maintenance clinics: A randomized controlled trial

Abstract: Objective-To determine if directly observed antiretroviral therapy (DOT) is more efficacious than self-administered therapy for improving adherence and reducing HIV viral load (VL) among methadone-maintained opioid users. Design-Two-group randomized trial.Setting-Twelve methadone maintenance clinics with on-site HIV care in the Bronx, New York. Participants-HIV-infected adults prescribed combination antiretroviral therapy. Intervention-24 weeks of DOT.Main outcomes measures-Between group differences at 4 asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
99
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(108 citation statements)
references
References 38 publications
8
99
1
Order By: Relevance
“…For example, two studies assess the effect of directly administered medication versus self-administered medication among substance abuse populations (integration of HIV services with substance abuse services) (Berg et al 2011;Macalino et al 2007). This impact evaluation compares directly administered medication, not the integration of HIV services with substance abuse services versus not integrating those services.…”
Section: Resultsmentioning
confidence: 99%
“…For example, two studies assess the effect of directly administered medication versus self-administered medication among substance abuse populations (integration of HIV services with substance abuse services) (Berg et al 2011;Macalino et al 2007). This impact evaluation compares directly administered medication, not the integration of HIV services with substance abuse services versus not integrating those services.…”
Section: Resultsmentioning
confidence: 99%
“…Berg and colleagues conducted a randomized trial using DOT to explore adherence behavior. The study indicated DOT enabled patients to maintain low viral loads and found they were more accepting of future medical evaluations and more likely to maintain ART adherence (17).…”
Section: The Self-motivation Adherence Strategymentioning
confidence: 99%
“…One of the suggested intervention models that can be implemented easily by healthcare providers is a personal telephone call or a short reminder message sent a few days before a scheduled medical appointment. This kind of direct, personal communication reminds the patient of the importance of the pending medical appointment (17). Computerized reminders also are highly cost-effective and can motivate higher levels of adherence among HIV patients.…”
Section: Behavior-specific Cognitions and Affectmentioning
confidence: 99%
See 2 more Smart Citations